The role of diagnostic wrist arthroscopy in suspected scapholunate ligament injury: a cohort study of 324 patients - Lyse van Wijk; Brigitte van der Heijden; J. S. Souer; Steven E. R. Hovius; Joost W. Colaris; on behalf of the Hand Wrist Study Group* (Bone & Joint Open)
Aims: Diagnostic wrist arthroscopy is considered the gold standard for evaluating wrist joint complaints. Although this tool is often used to diagnose and stage scapholunate ligament (SLL) lesions, reports about the possible findings and their clinical relevance are scarce. Therefore, this study describes the patient characteristics, arthroscopic findings, and treatment of patients who underwent diagnostic arthroscopy for suspected SLL injury. Methods: We conducted a retrospective cohort study of patients who underwent diagnostic wrist arthroscopy due to suspicion of a SLL lesion based on medical history, physical examination, and imaging. We systematically gathered arthroscopic findings and complications. Results: This study included 324 patients, predominantly male (55%), with a median age of 44 years (IQR 29 to 54) and symptom duration of ten months (IQR 5 to 24). The indication of SLL injury was arthroscopically confirmed in 253 patients (78%). Isolated SLL injuries were found in 92 patients (28%) (Geissler I/II: 32%; III: 37%; IV: 32%). SLL lesions and SLL-associated cartilage damage were discovered in 31 patients (10%). Additional findings were found in 181 patients (56%), such as triangular fibrocartilage complex lesions (36%), lunotriquetral ligament lesions (7%), and radioscaphocapitate ligament lesions (11%). No pathology was found in 20 patients (6%). In 27 patients (8%), complications occurred due to wrist arthroscopy. The most common follow-up surgeries were 3LT (40%), salvage procedures (9%), and ulnar shortening osteotomy (6%). Conclusion: While diagnostic wrist arthroscopy commonly confirms the suspected SLL lesions and their severity, it often reveals additional pathologies (un)related to the suspected pathology. It is essential to perform the procedure thoroughly to establish all possible pathologies. Determining the appropriate treatment for these additional findings is not always straightforward and needs further investigation. Cite this article: Bone Jt Open 2025;6(3):312–320.